Review of 'African Public Theology' - Gideon van der Watt (African Theological Journal for Church and Society)
This seminal book on African Public Theology appeared early in 2020, a year disrupted by the Coronavirus pandemic that – together with other crises of economic, political and ecological nature – is severely impacting the African Continent. More than ever this exceptional year laid bare the vulnerabilities of African countries and societies. All of this underscores the timely appearance and great importance of this book.